2012
DOI: 10.1111/j.1365-2648.2012.05958.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ knowledge and beliefs about care of older adults in a shifting context of nursing education

Abstract: Findings from this study suggest that even when integrated with general adult content, students' knowledge and beliefs about older adult care can be positively influenced. Furthermore research is needed to examine long-term integration of students' learning about older adult care. Nursing faculty with expertise in nursing care of older adults must develop resources and supports for their colleagues to build capacity among nurse educators and integrate older adult content throughout nursing programmes to enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 37 publications
(108 reference statements)
8
57
1
1
Order By: Relevance
“…Along the same lines, Baumbusch and colleagues 25 reported that students' knowledge and beliefs about adult care improved with 42 hours of theoretical courses and 14 hours of practical courses. Yank and colleagues 19 found that medical residents improved their confidence in using SMS after 26 however, reported that online educational programmes did not affect HCPs' knowledge, skills, or attitudes.…”
Section: After Attending the Educational And Practical Modulesmentioning
confidence: 79%
“…Along the same lines, Baumbusch and colleagues 25 reported that students' knowledge and beliefs about adult care improved with 42 hours of theoretical courses and 14 hours of practical courses. Yank and colleagues 19 found that medical residents improved their confidence in using SMS after 26 however, reported that online educational programmes did not affect HCPs' knowledge, skills, or attitudes.…”
Section: After Attending the Educational And Practical Modulesmentioning
confidence: 79%
“…Several researchers are investigating educational strategies to address ageist attitudes in nursing students [8][9][10], yet there is a dearth of educational strategies to make students' ageist attitudes explicit. In this study, the ROPE survey instrument was used to provide a snapshot of the prevalence of ageist behaviours as reported by first-year undergraduate nursing students.…”
Section: Resultsmentioning
confidence: 99%
“…While the need to address the stereotypical and often unfavourable perceptions of older people was identified 20 years ago [3], strategies to reduce ageism are not well developed in nursing curricula. Small studies have shown moderate improvements in student attitudes, through an integrated approach to the care of older people in undergraduate curricula [8], structured visits to older people for first-year nursing students [9], and high fidelity simulation [10].…”
Section: Introductionmentioning
confidence: 99%
“…There is need for continuing education on quality care to improve nursing practice in the care of the elderly [24]. If students are provided with the relevant education, they can deliver quality care and develop positive attitudes in caring for older people in their professional practice [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Total Knowledge score was also categorized as poor, average and good as per the score obtained by the subjects i.e. 9-14, 15-20, and [21][22][23][24][25][26][27] respectively. An informed consent was obtained from each subject.…”
Section: Methodsmentioning
confidence: 99%